Respuestas

2012-11-01T00:26:24+01:00

(9y^2 - 4 ) - (2y^2 - y ) \\\\ = 9y^2-4 - 2y^2 + y \\\\= 7y^2 + y - 4

 

(7y - 5)- (y-2)

 

7y - 5 - y + 2 

 

= 6y - 3 

 

 

(9a+5b+6c)-(6a+2b+3c)=

 

=9a +5b + 6c -6a - 2b -3c

 

= 3a + 3b + 3c 

 

 

  • Usuario de Brainly
2012-11-01T00:59:18+01:00

9y2-4y-2y2-y

(9y2-2y2)+(-4y-y)

7y2-5y

y(7y-5)

 

 

 

7y-5+y+2

(7y+y)+(2-5)

8y-3

 

 

9a+5b+6c-6a-2b-3c

(9a-6a)+(5b-2b)+(6c-3c)

3a+3b+3c

3(a+b+c)

 

3m2-7m+5-9m2-2m+1

-6m2-9m+6   todo por -1

6m2+9m-6

espero que te ayude